Narrative Review : Diet Patterns Against Coronary Artery Disease - Muh. Ahmad Aziri; Wisudawan, Wisudawan; Mir'atul Ginayah (Sean Institute, 2024)
Coronary Artery Disease (CAD) is the term for the buildup of plaque in the heart arteries which can cause a heart attack. Dieting is a person's conscious effort to limit and control the food they eat with the aim of reducing or maintaining body weight. The aim of the research is to determine the effect of dietary patterns on CAD using research database searches used in Pubmed, Science Direct, and Google Scholar over the last 5 years using the narrative review method. From the 9 journals examined, it was found that dietary patterns influence the risk of CAD. The reviewed evidence suggests that it is important to consider total dietary patterns for heart disease prevention. Dietary pattern-based research findings can be used to reduce risk factors for heart disease.